Horizontal transfer of OXA-23-carbapenemase-producing Acinetobacter species in intensive care units at an academic complex hospital, Durban, KwaZulu-Natal, South Africa. Issue 4 (2nd October 2017) - Swe-Han, Khine Swe; Pillay, Melendhran; Schnugh, Desmond; Mlisana, Koleka P; Baba, Kamaldeen; Pillay, Manormoney
Abstract: Introduction: Carbapenemase production is an important mechanism of carbapenem resistance in Acinetobacter species. This study investigated the presence of the carbapenem-hydrolysing class D β–lactamase- encoding genes, bla OXA-23 and bla OXA-58, and their association with the spread of multidrug-resistant (MDR) Acinetobacter species in intensive care units at an academic hospital. Method: Forty-four MDR Acinetobacter species were confirmed using VITEK ® 2 and Epsilometer tests. The bla OXA-23 and bla OXA-58 genes were detected by polymerase chain reaction (PCR) in twenty-four selected isolates. The bla OXA-23 amplicons were sequenced and compared to the GenBank database. Genotypic relatedness of isolates was determined by pulsed field gel electrophoresis (PFGE). Clinical and laboratory data were analysed. Results: Among the twenty-four isolates, eighteen were carbapenem resistant and six were sensitive. The bla OXA-23 gene, but not bla OXA-58, was detected in the eighteen resistant strains. The bla OXA-23 amplicons showed 100% identity with the GenBank database of bla OXA-23 . The MICs of carbapenems against Acinetobacter species carrying the bla OXA-23 gene were 8 to > 16 μg/ml. Genetic relatedness was evident among isolates of seven pairs from fourteen patients. Of these patients, twelve were in the same ICUs and two were adjacent to another ICU during the same hospitalisation period. Conclusion: The selected MDR Acinetobacter species carried the bla OXA-23 gene responsible for resistance to carbapenems, while molecular and clinical data analysis suggested horizontal transmission in ICUs. In addition, the PFGE typing of a diverse collection of MDR Acinetobacter species clones showed that isolates were related to no more than two patients, suggesting that no outbreak had occurred.